2021
DOI: 10.1088/1742-6596/1805/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Application Titanium Dioxide Nanotube from Natural Source as Tooth Whitening

Abstract: Nanotube material that has been synthesized for decades is Titanium Dioxide Nanotube (TDN) because it has high photocatalytic properties and produces free radicals that can whiten teeth. Tooth whitening materials that are used in the public is such as H2O2 with high concentrations so that they endanger the health of tooth enamel. Therefore, this research uses TDN as a natural teeth whitening agent with low H2O2 concentrations. TDN is obtained from natural materials, mineral sand which is chemically processed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the Istiqomah study, titanium dioxide nanotubes (TDN) were mixed with 3 % H 2 O 2 and used as a tooth-whitening agent. The collected results showed that the prepared composite brightened the appearance of teeth by generating O 2 − radicals [ 31 ]. Hamza and colleagues investigated TiO 2 NPs as a teeth-whitening agent in two different concentrations (5 % and 10 % TiO 2 ).…”
Section: Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Istiqomah study, titanium dioxide nanotubes (TDN) were mixed with 3 % H 2 O 2 and used as a tooth-whitening agent. The collected results showed that the prepared composite brightened the appearance of teeth by generating O 2 − radicals [ 31 ]. Hamza and colleagues investigated TiO 2 NPs as a teeth-whitening agent in two different concentrations (5 % and 10 % TiO 2 ).…”
Section: Nanomaterialsmentioning
confidence: 99%
“…H 2 0 2 is a non-stable reagent that can cause several side effects, such as soft tissue irritation, tooth sensitivity, and the ability to inhibit pulpal enzymes. Therefore, there is a demand for an enhanced alternative and a low-cost option to teeth whitening [ 31 ].…”
Section: Introductionmentioning
confidence: 99%